Measurement of vapor-liquid equilibria for the binary mixture of propylene (R-1270)+1,1,1,2-tetrafluoroethane (HFC-134a) - Ho, QN; Lee, BG; Park, JY; Kim, JD; Lim, JS (ELSEVIER SCIENCE BV, 2004)
Isothermal vapor-liquid equilibria data for the binary mixture of propylene (R-1270) + 1,1,1,2-tetrafluoroethane (HFC-134a) at five equally spaced temperatures between 273.15 and 313.15 K were measured by using a circulation-type equilibrium apparatus. The experimental data were correlated with the Peng-Robinson equation of state (PR-EOS) combined with the Wong-Sandler mixing rule. It was confirmed that the data calculated by this equations of state had a good agreement with experimental data. In addition, we used a simple equation obtained from the fundamental equation of phase equilibrium and NRTL activity coefficient model to approximately evaluate the azeotropic points of this mixture at investigated temperatures. A small difference between experimental azeotropic points and calculated ones corresponding to non-randonmess parameter alpha equal to 0.2 was found. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: MIXING RULE; STATE; EQUATION